1982
DOI: 10.1111/j.1469-8137.1982.tb03347.x
|View full text |Cite
|
Sign up to set email alerts
|

Interaction of Light Intensity and Soil Temperature With Phosphorus Inhibition of Vesicular‐arbuscular Mycorrhiza Formation

Abstract: SUMMARYThe interaction between light intensity and soil temperature with phosphorus inhibition of vesicular-arbuscular mycorrhiza (VAM) formation in sudangrass (Sorghum vulgare, Pers.) was investigated in P-deficient (0-5 mg P kg~^) sandy soil amended with 0 (OP), 15 (15P) and 30 (30P) mg P kg"' soil as superphosphate. For seedlings inoculated with Glomus fasciculatus and grown at 100, 75, and 50"0 of glasshouse light intensity, the reduction in VAM formation by added soil P (15 P and 30P) was greatest at the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
50
2

Year Published

1990
1990
2019
2019

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 100 publications
(59 citation statements)
references
References 15 publications
(21 reference statements)
5
50
2
Order By: Relevance
“…In contrast with our observations, early studies showed that P inhibition decreases the numbers of vesicles Stribley et al, 1980;Abbott et al, 1984;Amijee et al, 1989: Bruce et al, 1994 and lengths of colonized regions (Sanders and Tinker, 1973;Jasper et al, 1979;Buwalda et al, 1982;Graham and Leonard, 1982;Smith, 1982;Amijee et al, 1989;Miranda et al, 1989;Smith and Gianinazzi-Pearson, 1990;Braunberger et al, 1991;Thomson et al, 1991;Baon et al, 1992;Bruce et al, 1994;Tawaraya et al, 1994). However, reduced intraradical fungal Figure 6.…”
Section: Short-term P Inhibition Versus Long-term P Inhibitioncontrasting
confidence: 99%
“…In contrast with our observations, early studies showed that P inhibition decreases the numbers of vesicles Stribley et al, 1980;Abbott et al, 1984;Amijee et al, 1989: Bruce et al, 1994 and lengths of colonized regions (Sanders and Tinker, 1973;Jasper et al, 1979;Buwalda et al, 1982;Graham and Leonard, 1982;Smith, 1982;Amijee et al, 1989;Miranda et al, 1989;Smith and Gianinazzi-Pearson, 1990;Braunberger et al, 1991;Thomson et al, 1991;Baon et al, 1992;Bruce et al, 1994;Tawaraya et al, 1994). However, reduced intraradical fungal Figure 6.…”
Section: Short-term P Inhibition Versus Long-term P Inhibitioncontrasting
confidence: 99%
“…In the past, several treatments have been used to separate efiects of the concentrations of soluble carbohydrates in roots and root exudates and the concentrations of P in roots on the formation of VA mycorrhizas: photon flux, soil temperature (Graham, Leonard & Menge, 1982;Same et al, 1983), defoliation (Same et al, 1983), photoperiod (Johnson et al, 19826), ozone stress (McCool & Menge, 1983), simazine application (Schwab, Johnson & Menge, 1982), flower bud initiation (Johnson et al, 1982 a) and sulphur supply (Thomson, Robson & Abbott, 1985). In our study, subterranean clover was grown at two trradiances and two concentrations of soil P in an attempt to vary the concentrations of soluble carbohydrates in roots independently of the concentrations of P in roots.…”
Section: Introductionmentioning
confidence: 99%
“…Light and developmental status of the plant may also affect colonization. Altered carbon flow to the root system may result from low-light-intensity photosynthesis (Ferguson and Menge, 1982;Graham et al, 1982) or redirection to support the energy demands of flowering (Johnson et al, 1982). Other compounds from plant roots may also affect colonization.…”
mentioning
confidence: 99%